Answer:
1a) Length = 7x + 3 & Width = 4x - 2
1b) Area =
![28x^2 -2x -6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lnmujiufa7gb3omhtj0z6psm3a0y3vq9rl.png)
1c) Area = 2774 sq. m
2.
![(x-4)(y+7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lnb1i7x7hey2toglz46pab60y338851wiu.png)
Explanation:
1a)
The length given as words is "3 more than 7 times x"
The width given as words is "4 times x minus 2"
The expression for length would be 7x + 3
The expression for width would be 4x - 2
1b)
The area is length * width
Since we already know the algebraic expressions for length and width from part (a) above, we use the formula:
Area = (7x+3)(4x-2) = 28x^2 -14x + 12x - 6 = 28x^2 -2x -6
Area =
![28x^2 -2x -6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lnmujiufa7gb3omhtj0z6psm3a0y3vq9rl.png)
1c)
Given x = 10, we put this into the area expression we found in (b) above.Let's see:
![28x^2 -2x -6\\=28(10)^2 -2(10) -6\\=2774](https://img.qammunity.org/2020/formulas/mathematics/middle-school/druydxam58kx8mc3x6d1s8ufkodqgw3vmr.png)
Area = 2774 sq. m
2.
We can group the first two terms and next two terms and write up:
![xy-4y+7x-28\\(xy-4y)+(7x-28)\\y(x-4)+7(x-4)\\(x-4)(y+7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ltjkcuxpjhy2li57u2www6ksb8yvdvk4ft.png)
That's the factored form.